Characterization of polydimethylsiloxane rubber upon photochemical, thermal, salt-fog ageings and exposure to acid vapours - Delor-Jestin, Florence; Tomer, N. S.; Singh, R. P.; Lacoste, Jacques (E-Polymers, 2006)
The changes in the chemical structure and the physical properties of a filled crosslinked polydimethylsiloxane rubber were monitored as a function of various ageing factors. The variables included photochemical, thermal, salt-fog ageings and exposure to acid vapours. Unaged and aged samples were studied by IR spectroscopy, hardness measurements, Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) coupled with IR spectroscopy. No significant oxidation was detected after all ageings, except for nitric acid treatment. The presence of aluminium trihydrate was clearly identified as responsible for the observed chemical changes. Then an important vulnerability of this filled silicone rubber towards the cross-linking reactions provoked by usual ageings was also detected. The DSC-thermoporosimetry measurements of the mesh size distribution gave a comparison of cross-linking densities for each ageing. The complementary analysis with TGA-IR allowed us to differenciate the thermal stability of the formulation after various ageings and to acquire new knowledge about thermal decomposition.

Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry